Optimizing plasmonic gold nanorod deposition on glass surfaces for high-sensitivity refractometric biosensing - Hwang, Youngkyu (2023)
Owing to high surface sensitivity, gold nanorods (AuNRs) are widely used to construct surface-based nanoplasmonic biosensing platforms for label-free molecular diagnostic applications. A key fabrication step involves controlling AuNR deposition onto the target surface, which requires maximizing surface density while minimizing inter-particle aggregation, and is often achieved by surface functionalization with a self-assembled monolayer (SAM) prior to AuNR deposition. To date, existing studies have typically used a fixed concentration of SAM-forming organic molecules (0.2-10% v/v) while understanding how SAM density affects AuNR deposition and resulting sensing performance would be advantageous. Herein, we systematically investigated how controlling the (3-aminopropyl)triethoxysilane (APTES) concentration (1-30% v/v) during SAM preparation affects the fabrication of AuNR-coated glass surfaces for nanoplasmonic biosensing applications. Using scanning electron microscopy (SEM) and UV-visible spectroscopy, we identified an intermediate APTES concentration range that yielded the highest density of individually deposited AuNRs with minimal aggregation and also the highest peak wavelength in aqueous solution. Bulk refractive index sensitivity measurements indicated that the AuNR configuration had a strong effect on the sensing performance, and the corresponding wavelength-shift responses ranged from 125 to 290 nm per refractive index unit (RIU) depending on the APTES concentration used. Biosensing experiments involving protein detection and antigen-antibody interactions further demonstrated the high surface sensitivity of the optimized AuNR platform, especially in the low protein concentration range where the measurement shift was ~8-fold higher than that obtained with previously used sensing platforms.